Bictegravir-Based Antiretroviral Therapy-Associated Accelerated Hyperglycemia and Diabetes Mellitus. (16th April 2021) - Nolan, Nathanial S; Adamson, Samantha; Reeds, Dominic; O'Halloran, Jane A
Abstract: Integrase strand transfer inhibitor (INSTI)-based antiretroviral therapy (ART) is first line for treatment of people with human immunodeficiency virus (PWH). Emerging data suggest the possibility of adverse metabolic effects of these medications. We describe 3 cases in which PWH developed hyperglycemia and ketoacidosis within months of being switched to bictegravir-based ART. Abstract : We provide increased awareness among clinicians of the potential for antiretroviral therapy-associated hyperglycemia with bictegravir-containing regimens.